Effect of adsorbents on diets with corn contaminated by mycotoxins on the productive performance and health of broilers - Fernandes, Jovanir Inês Müller; Baldo, Jessiane Sauer; Ferreira, Ana Clara Polo; Schuroff , Juliana Schulter; Reuter, Anderson Henrique; Salinas, Bruna Carolina Druzian (Acta Scientiarum. Animal Sciences, 2021)
A total of 1,296 broiler chicken were housed, distributed in a completely randomized design with 6 treatments and 6 repetitions. The treatments consisted of a control diet formulated with corn considered adequate and without the addition of adsorbent, a diet formulated with corn naturally contaminated with mycotoxin (CCM) and four diets formulated with CCM and added with different commercial adsorbents. At the end of the first week and at 21 days of age of the birds, it was observed that the control diet resulted in greater (p < 0.05) live weight and weight gain in relation to the inclusion of CCM. The relative weight of the liver was lower for the control group compared to the groups receiving a diet with CCM and CCM + ads D. The relative weight of the proventriculus and cloacal bursa was lower for the control group compared to those who received a diet with CCM + ads B and CCM + ads C. There was no significant effect (p > 0.05) of the diets on the analysis of serum biochemistry and the occurrence of fatty and hydropic degeneration in the liver of broilers. The use of adsorbents can mitigate the harmful effects of mycotoxins, however, these products have specific binding capacity to the type of mycotoxin present in food.